Diversity of sacrifice : form and function of sacrificial practices in the ancient world and beyond - Murray, Carrie Ann, 1976- (State University of New York Press, 2016)
"Explores sacrificial practices across a range of contexts from prehistory to the present. The term 'sacrifice' belies what is a complex and varied transhistorical and transcultural phenomenon. Bringing together scholars from such diverse fields as anthropology, archaeology, epigraphy, literature, and theology, Diversity of Sacrifice explores sacrificial practices across a range of contexts from prehistory to the present. Incorporating theory, material culture, and textual evidence, the volume seeks to consider new and divergent data related to contexts of sacrifice that can help broaden our field of vision while raising new questions. The essays contributed here move beyond reductive and simple explanations to explore complex areas of social interaction. Sacrifice plays a key role in the overlapping sacred and secular spheres for a number of societies in the past and present. How religious beliefs and practices can be integral parts of life on individual and community levels is of fundamental importance to understanding the past and present. In addition to aiding scholarly research, Diversity of Sacrifice enables students to explore this rich theme across Europe and the Mediterranean with clear discussions of theory and data"--Publisher's website
Papers from a conference held as the annual symposium for the Institute for European and Mediterranean Archaeology (IEMA) at the University at Buffalo, SUNY, in 2011.
Keywords: Sacrifice -- Europe -- History -- To 1500 -- Congresses.; Sacrifice -- Mediterranean Region -- History -- To 1500 -- Congresses.; Social archaeology -- Europe -- Congresses.; Social archaeology -- Mediterranean Region -- Congresses.; Archaeology and religion -- Europe -- Congresses.; Archaeology and religion -- Mediterranean Region -- Congresses.; Material culture -- Europe -- History -- To 1500 -- Congresses.; Material culture -- Mediterranean Region -- History -- To 1500 -- Congresses.; Social interaction -- Europe -- History -- To 1500 -- Congresses.; Social interaction -- Mediterranean Region -- History -- To 1500 -- Congresses.; Electronic books.; Archéologie sociale -- Europe -- Congrès.; Archéologie et religion -- Europe -- Congrès.; Livres numériques.; e-books.; RELIGION -- Reference.; Archaeology and religion; Material culture; Sacrifice; Social archaeology; Social interaction; Europe; Mediterranean Region; To 1500; Conference papers and proceedings; History